NILAI-NILAI KARAKTER PADA BUKU TEMATIK SISWA KURIKULUM 13 KELAS IV SDN HARAPAN BARU III KOTA BEKASI - Dariyanto Dariyanto; Awiria Awiria (Almarhalah | Jurnal Pendidikan Islam, 2022)
The purpose of this study is to describe the values of character education in the thematic books for fourth grade students. Character education is the foundation must be designed and developed in student textbooks. The quality of the book content will lead students to the educational goals in the curriculum. This research is a content analysis research with the thematic book subject for fourth grade students, it tries to focus on the character values contained there. The results showed that in five thematic books, fourth grade students in semester I had explicitly and implicitly developed seven character values: religious, honest, disciplined, responsible, confident, polite and caring. Religious character values have the lowest frequency, while other character values are developed more intensively by providing actual models and examples in life. Keywords: character education values, thematic books, curriculum 13